Community Structure of Coral Reef Ecosystem in Senoro-Toili Block - Kasim Mansyur; Achmad Rizal; Musayyadah Tis’in; Muh. Saleh Nurdin; Shanti Nata Artha; Enrico Putra Nurdin; Clara Maulidiansa; Abdil Halimis Stani (UIN Sunan Gunung Djati Bandung, 2026)
Research on coral reef biodiversity within oil and gas operational areas remains limited, as most previous studies have focused on coastal ecosystems adjacent to urban environments. This study aims to assess coral reef condition and reef fish community structure in the Senoro–Toili Block, and to examine the relationship between coral cover and reef fish abundance. Field data were collected using Manta Tow and Line Intercept Transect (LIT) methods for coral reef conditions, while reef fish data were obtained through the Underwater Visual Census (UVC) method. Coral reef observations included percentages of live hard coral, dead coral, algae, and abiotic substrates. Fish data comprised species composition and abundance, which were analyzed at the family level. The relationship between reef fish abundance and live coral cover was tested using Pearson correlation analysis. The study results indicated that dead corals dominated the Senoro-Toili Block coral community, ranging from 17.62 to 52.68%. Evaluation of coral reef conditions shows moderate to high levels of damage, with a high mortality index, indicating that reef health is significantly compromised and may negatively impact associated reef fish populations. The reef fish community comprises 195 species across 37 families. The abundance of reef fish ranges from 1605 to 3105 individuals/500 m². The Pearson correlation showed a significant association between reef fish abundance and coral cover (p < 0.05). The diversity index was high, and the evenness index indicated a stable fish community. A low dominance index supported this. These conditions indicate that the reef fish community in the Senoro–Toili Block exhibits relatively high ecological resilience in response to both natural and anthropogenic disturbances. These results highlight the need for continuous management interventions, especially coral transplantation initiatives implemented in the study region.